RC walls in Australia: reconnaissance survey of industry and literature review of experimental testing. Issue 1 (2nd January 2017) - Menegon, S. J.; Wilson, J. L.; Lam, N. T. K.; Gad, E. F.
Abstract: This paper presents the findings of a recent reconnaissance survey of the reinforced concrete (RC) construction industry in Australia. The survey involved the review of the structural documentation of a set of case study buildings constructed in Australia. The types of walls and observed methods of detailing are documented. Upper and lower bound values for typical wall attributes have been presented which researchers can utilise to design laboratory test specimens or perform parametric computer studies, to ensure their study accurately represents real-world conditions. A literature review of experimental testing of the lateral in-plane capacity of RC walls is included. The literature review identified 81 experimental studies, in which 501 RC wall test specimens have been tested worldwide. It is shown that very little experimental studies have been performed on RC walls that match what is being constructed in Australia.